Proteinase K-pretreated ConA-based ELISA assay: a novel urine LAM detection strategy for TB diagnosis - Huang, Huan; Qu, Rong; Wu, Kang; Xu, Jinchuan; Li, Jianhui; Lu, Shuihua; Sui, Guodong; Fan, Xiao-Yong (Frontiers in Microbiology, 2023)
Objectives: Lipoarabinomannan (LAM), an abundant cell wall glycolipid of mycobacteria including Mycobacterium tuberculosis (Mtb), is a promising TB diagnostic marker. The current commercially available urine LAM assays are not sufficiently sensitive, and more novel detection strategies are urgently needed to fill the current diagnostic gap.: A proteinase K-pretreated Concanavalin A (ConA)-based ELISA assay was developed. Diagnostic performance was assessed by several bacterial strains and clinical urine samples.Results: The assay's limit of detection (LoD) against ManLAM was 6 ng/mL. The assay reacted strongly to Mtb H37Rv and M. bovis BCG, intermediately to M. smegmatis mc 2 155, and weakly to four non-mycobacteria pathogens. This method could distinguish TB patients from healthy controls (HCs) and close contacts (CCs) in 81 urine samples treated with proteinase K, which increases urine LAM antibody reactiveness. In TB + HIV + and TB + HIV - patients, the sensitivity was 43.8% and 37.5%, respectively, while the specificity was 100.0%.The areas under ROC curves (AUCs) were 0.74 and 0.82, respectively.This study implies that ConA can be paired with antibodies to detect LAM.Proteinase K treatment could effectively enhance the sensitivity by restoring the reactiveness of antibodies to LAM.